Motor learning from virtual reality to natural environments in individuals with Duchenne muscular dystrophy. - Quadrado, Virgínia Helena; Silva, Talita Dias da; Favero, Francis Meire; Tonks, James; Massetti, Thais; Monteiro, Carlos Bandeira de Mello (Disability & Rehabilitation: Assistive Technology, 2019)
Purpose: To examine whether performance improvements in the virtual environment generalize to the natural environment. Study design: we had 64 individuals, 32 of which were individuals with DMD and 32 were typically developing individuals. Methods: The groups practiced two coincidence timing tasks. In the more tangible button-press task, the individuals were required to 'intercept' a falling virtual object at the moment it reached the interception point by pressing a key on the computer. In the more abstract task, they were instructed to 'intercept' the virtual object by making a hand movement in a virtual environment using a webcam. Results and Conclusions: For individuals with DMD, conducting a coincidence timing task in a virtual environment facilitated transfer to the real environment. However, we emphasize that a task practiced in a virtual environment should have higher rates of difficulties than a task practiced in a real environment. IMPLICATIONS FOR REHABILITATION: Virtual environments can be used to promote improved performance in ?real-world? environments. Virtual environments offer the opportunity to create paradigms similar ?real-life? tasks, however task complexity and difficulty levels can be manipulated, graded and enhanced to increase likelihood of success in transfer of learning and performance. Individuals with DMD, in particular, showed immediate performance benefits after using virtual reality